SYSTEM OF CONTINUOUS TRAINING OF ELEMENTARY SCHOOL TEACHERS TO WORK WITH THE GIFTED STUDENTS: EXPERIMENTAL RESEARCH - Ірина Гавриш; Вікторія Ушмарова; Олександра Холтобіна (National Academy of Educational Sciences of Ukraine, 2021)
The study investigates the preparation of elementary school teachers for working with gifted students, and the process of its formation in the system of continuous pedagogical education. The methodological, theoretical and methodological principles of the study are presented. The study theoretically substantiated the main principles of the elementary school teachers' preparation to work with gifted students. Core components are demonstrated to be motivational, cognitive, activity, reflexive and personal. The author's scientific-methodical system of forming readiness elementary school teachers to work with gifted students in the conditions of continuous pedagogical education are presented The stages of its realization are determined and the effectiveness of implementation of the said system is experimentally proved. The criteria, indicators and levels of preparedness of elementary school teachers to work with gifted students are clarified.